2015
DOI: 10.1074/jbc.m115.673566
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Hyaluronan (HA) Metabolism Mediated by HYBID (Hyaluronan-binding Protein Involved in HA Depolymerization, KIAA1199) and HA Synthases in Growth Factor-stimulated Fibroblasts

Abstract: Regulation of hyaluronan (HA) synthesis and degradation is essential to maintenance of extracellular matrix homeostasis. We recently reported that HYBID (HYaluronan-Binding protein Involved in hyaluronan Depolymerization), also called KIAA1199, plays a key role in HA depolymerization in skin and arthritic synovial fibroblasts. However, regulation of HA metabolism mediated by HYBID and HA synthases (HASs) under stimulation with growth factors remains obscure. Here we report that TGF-␤1, basic FGF, EGF, and PDGF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
87
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 79 publications
(95 citation statements)
references
References 34 publications
8
87
0
Order By: Relevance
“…The signal transduction pathways of PDGFRb (43), LPA 1 (44), and EGFR (45) have all previously been shown to involve the b-arrestins, suggesting that non-cell autonomous fibroblast invasion driven by these mediators will depend on b-arrestin1 and/or -2 as well. Similarly, PDGF-BB, FGF-2, and EGF have all been shown to induce HAS2 expression in human fibroblasts (46), as has LPA (47), suggesting that the HAS2-HA-CD44 pathway described for cell-autonomous invasion may also contribute to the non-cellautonomous fibroblast invasion that we describe here. We believe that further elaboration of the common molecular mechanisms that drive non-cell-autonomous fibroblast invasion in pulmonary fibrosis has the potential to provide a rich set of drug targets for the treatment of IPF and other fibrotic lung diseases.…”
Section: Discussionsupporting
confidence: 68%
“…The signal transduction pathways of PDGFRb (43), LPA 1 (44), and EGFR (45) have all previously been shown to involve the b-arrestins, suggesting that non-cell autonomous fibroblast invasion driven by these mediators will depend on b-arrestin1 and/or -2 as well. Similarly, PDGF-BB, FGF-2, and EGF have all been shown to induce HAS2 expression in human fibroblasts (46), as has LPA (47), suggesting that the HAS2-HA-CD44 pathway described for cell-autonomous invasion may also contribute to the non-cellautonomous fibroblast invasion that we describe here. We believe that further elaboration of the common molecular mechanisms that drive non-cell-autonomous fibroblast invasion in pulmonary fibrosis has the potential to provide a rich set of drug targets for the treatment of IPF and other fibrotic lung diseases.…”
Section: Discussionsupporting
confidence: 68%
“…HA is synthesized by HA synthases (HAS1, HAS2, and HAS3), among which HAS1 and HAS2 play a key role in HA production in human normal skin fibroblasts . We have recently reported that HYBID (HYaluronan Binding protein Involved in hyaluronan Depolymerization, KIAA1199) plays an essential role in HA degradation in human normal skin fibroblasts . Our recent study also demonstrated that in the Japanese women, HYBID is overexpressed in the photoexposed skin compared with the photoprotected skin and up‐regulation of HYBID is correlated with HA reduction in the papillary dermis of the photoexposed skin, showing positive correlations with skin wrinkling and sagging .…”
Section: Introductionmentioning
confidence: 90%
“…RNA extraction, cDNA synthesis and a TaqMan real‐time polymerase chain reaction assay were performed as described previously . The relative quantification values of HYBID , HAS1 , HAS2 , HYAL1 , HYAL2 , CD44 and TGFBR2 were normalized to endogenous 18S rRNA.…”
Section: Methodsmentioning
confidence: 99%